Evaluating the Liberia Revenue Code: A Strategic Framework for Combating Illicit Financial Flows and the Informal Sector (London Journal of Research In Management & Business, 2025)
This paper critically examines the Liberia Revenue Code (LRC) for its efficiency in revenue collection and its capacity to address illicit financial flows (IFFs) and the informal sector. It explores how weaknesses in policy design, enforcement mechanisms, and institutional capacity have limited the Codes effectiveness in reversing revenue losses and expanding the formal tax base. Drawing on relevant fiscal, legal, and economic literature as well as practical developments within the Liberian context, the analysis demonstrates that while the LRC provides a foundational tax framework, it lacks the structural provisions to effectively combat the twin challenges of IFFs and informality. The proliferation of unregulated financial activities and informal enterprises continues to erode Liberias tax base, undermining efforts to achieve economic stability, equity, and development. The paper calls for the development and implementation of a national strategy anchored on empirical research, institutional strengthening, legal reforms, and digital innovations to ensure greater fiscal sustainability, improved compliance, and a formalized economic environment conducive to national development. It argues that without strategic intervention, the fiscal cost of these phenomena will continue to widen, and the state will remain handicapped in delivering on its developmental mandate.
Keywords: Nigeria; Cybersecurity threats; demand/supply side of financial inclusion; and OLS/2SLS/GMM